The Analysis of Bullying Experienced By Eleanor in Rainbow Rowell's Eleanor & Park. - Santosa Santosa (Acitya: Journal of Teaching and Education, 2022)
The aim of this research is to comprehend bullying types and its effects experienced by the main character of Eleanor in Rainbow Rowell’s novel, Eleanor & Park. The writer utilized the psychological approach that applied theories in psychology to analyze, examine and understand bullying experienced of the main character. The method of this analysis was descriptive qualitative method, which tried to analyze bullying experienced by the main character. The writer discovered that the types of bullying experienced by Eleanor are physical bullying, verbal bullying, and sexual bullying. Meanwhile, the effects of bullying experienced by the main character are such as feeling of shame, low self-esteem, symptoms of depression, and suicidal thought.